Advances in Fundamental and Applied Research on Spatial Audio - Katz, Brian F.G; Majdak, Piotr (IntechOpen, 2022)
Spatial audio is a dynamic and rapidly evolving field, as it is closely linked to advances in computer technology and digital signal processing. The democratization of virtual reality hardware available as consumer devices has moved the field further out of traditional laboratory research, and directly into applied research targeting a wide range of consumers. Advances in Fundamental and Applied Research on Spatial Audio presents a collection of eight peer-reviewed chapters on this exciting area of research. The contributions are organized into three sections: "Acoustic Methodology", "Perception", and "Applications", and cover a range of topics, addressing both headphone- and loudspeaker-based reproductions, offering both methodological overviews and specific case studies.